On Age Criteria of Juvenile Criminal Responsiblity - I. A. Kuznetsova; A. V. Kuznetsov (Сибирское юридическое обозрение, 2012)
The article deals with the problem of juvenile criminal responsibility criteria in the RF criminal legislation. The authors offer the ways of solving some disputable issues.